Gades and the Mediterranean: a Process of Integration - dos Santos Silva, Bruno (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
The impetus for this paper is to present possible contributions of the Network Theory approach to the analysis of the Roman presence in Turdetania by the end of the 1st millennium BC. Firstly, we discuss how some written sources, such as Strabo’s Geography, describe this region and how the countryside and coastal areas are mentioned. Secondly, we present how contemporary historiography makes use of Network Theory to investigate numerous issues of Ancient History. Finally, we point out a proposal for Social Network Analysis (SNA) to questions regarding Turdetania before and after Roman occupation.